The Thirsty Traveler and Luck-Free Moral Luck. - Kahn, Samuel (Problems / Problemos, 2024)
This article is divided into three sections. In the first and second sections, I examine Sartorio's account of the causal structure of the famous Thirsty Traveler thought experiment. I argue that this account does not withstand critical scrutiny. In the third section, I turn to a novel kind of moral luck that Sartorio uses the Thirsty Traveler to expose. I expand the scope of my argument to look also at other recently proposed categories of moral luck. I argue that these proposals are overhasty.